2011
DOI: 10.4021/jnr71e
|View full text |Cite
|
Sign up to set email alerts
|

The Efficiency of Intravenous Theophylline on the Headache Which Occurs After Spinal Anesthesia

Abstract: Background: Headache which occurs after spinal anesthesia is the most frequent complication (30 -40%). In our study, we studied the efficiency of intravenous theophylline application on the patients who came with after spinal anesthesia headache (ASAH).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…It has been reported that the use of theophylline for PDPH should be repeated in different studies. In one study, it was reported that 6 patients (35.3%) with a VAS value of <50% needed a second theophylline infusion and in the other study, 5 (25%) of 20 patients required second theophylline infusion (12,23) . In our study, 22 (33.8%) patients received more than one infusion.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…It has been reported that the use of theophylline for PDPH should be repeated in different studies. In one study, it was reported that 6 patients (35.3%) with a VAS value of <50% needed a second theophylline infusion and in the other study, 5 (25%) of 20 patients required second theophylline infusion (12,23) . In our study, 22 (33.8%) patients received more than one infusion.…”
Section: Discussionmentioning
confidence: 98%
“…There were 6 studies evaluating theophylline activity in PDPH in our literature search (12,13,23,24) . Theophylline was administered intravenously in 4 of these studies and orally in 2 of them.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations